Impact of 1998 Economic Crisis on the Dynamics of Market Reforms and the Privatization Process in Russia (on the Example of St. Petersburg) - T. V. Valov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The impact of the 1998 financial crisis on the dynamics of market reforms and the privatization process in Russia and St. Petersburg is examined in the article. The activity of the government aimed at curbing the crisis tendencies in the first half of 1998, as well as the activity of the Cabinet of E. M. Primakov on the reanimation of the Russian economy in September — December 1998, is analyzed. The main reasons for the default, the impact of the crisis on privatization activity, the state of industrial enterprises, the banking sector, the transformation of integrated business groups, the level of welfare of the population, the state of relations “center-regions” are considered, and the social reaction to these changes is investigated. The state of the industry is revealed on the example of St. Petersburg enterprises. The approaches of the government of E. M. Primakov to the privatization policy are investigated. The features of personnel policy in the Ministry of State Property of the Russian Federation and the Committee for the Management of City Property of St. Petersburg are considered. The study of the causes and consequences of the default showed that this event became a key event in the development of the Russian economy, significantly influenced the pace of privatization activity and the state of financial and industrial groups, and also became the starting point for subsequent economic growth.